Private bill procedure?(the Scotch Act of 1899) - Samuels, Arthur W. (Statistical and Social Inquiry Society of Ireland, 1900)
Rarely has there been such a waste of Irish capital in Westminster as there has this year been. Hardly even have the efforts of promoters proved so futile, and of opponents so exhausting. The shareholders of some of the most prosperous and of some of the least prosperous of Irish Railways have alike to deplore the dissipation in Parliamentary litigation of their profits for 1899. The ratepayers of Dublin, of Rathmines, of Pembroke, of Clontarf, and other suburbs of the City, long will feel the burden added to their rates by the London litigation of the Session that has past.
Read Tuesday, November 28th, 1899
Keywords: Private bill legislation; Expenditure; 314.15